2008
DOI: 10.1111/j.1471-0528.2008.01936.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the local immune responses in cervical intraepithelial neoplasia: a cross‐sectional and longitudinal analysis

Abstract: Introduction Immunological competence influences the progression of cervical intraepithelial neoplasia (CIN) to invasive cancer. Information on the local immunological changes during the natural course of CIN is central for the development of new therapies.Objective This study defines the populations of tissue-infiltrating immune cells in a cross-sectional cohort of different grades of CIN and also in a longitudinal cohort of regressing, persistent and progressing low-grade (LG)-CIN.Design A cohort of 125 wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 38 publications
1
52
0
8
Order By: Relevance
“…In a 12-month prospective study of histologically confirmed CIN1 lesions, regression during the study period was strongly correlated with the presence at study entry of intraepithelial granzyme B ϩ CD8 ϩ and granzyme B ϩ CD56 ϩ cells (79). Immunohistochemical studies showed CD8 ϩ T cells expressing the ␣4/␤7 integrin to be present in CIN1/koilocytic cervical lesions but absent or present in reduced numbers in CIN3 lesions (45).…”
Section: Immune Response To Hpv In Natural Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 12-month prospective study of histologically confirmed CIN1 lesions, regression during the study period was strongly correlated with the presence at study entry of intraepithelial granzyme B ϩ CD8 ϩ and granzyme B ϩ CD56 ϩ cells (79). Immunohistochemical studies showed CD8 ϩ T cells expressing the ␣4/␤7 integrin to be present in CIN1/koilocytic cervical lesions but absent or present in reduced numbers in CIN3 lesions (45).…”
Section: Immune Response To Hpv In Natural Infectionsmentioning
confidence: 99%
“…With neoplastic transformation and genomic instability, the expression of key cytokines, adhesion molecules, chemokines, and chemokine receptors on the infected epithelium and on the underlying microvascular endothelium of the stroma is deregulated (14,15), resulting in the downregulation of key receptors essential for the ingress of antigen-specific T cells and other cytotoxic effectors into the epithelium (74). Thus, even if HPV antigen-specific cytotoxic cells have been generated, their ingress into the epithelium is poor and regulatory T cells increasingly dominate the lesions and abrogate the killer effector response (40,41,79).…”
Section: Immune Responses Are Deregulated During Hpv-associated Neoplmentioning
confidence: 99%
“…It is of interest that elevated ORs were present when comparing SCC with lesions of all grades, suggesting that this is a phenomenon associated with invasion and not with persistent infection or development of precursor lesions. Given the fact that CD8+ cells presented the highest coefficient variation, and that there was lack of agreement when the dispersion of the measurements was compared, we also estimated the ORs using the counting conducted by each pathologist to estimate the average number of cells/mm 2 [14,15,30,31]. However since the confidence intervals were wide, studies with bigger sample size may help to confirm the accuracy of our observation.…”
Section: Discussionmentioning
confidence: 98%
“…Immune response has been considered a cofactor that may play a role in the different stages of the natural history of cervical cancer [13]. Although tumor infiltrates lymphocytes (TILs) have been observed in pre neoplastic and tumor tissues [14][15][16][17], it has been difficult to delineate the role that these immune cells may play in affording the regression of different grades of CIN. Studies have reported an equal proportion of CD4+ and CD8+ cells in the stroma of pre-neoplastic lesions and a low density of CD4+ cells in the epithelium of pre-neoplastic lesions when compared to normal tissues [18].…”
Section: Introductionmentioning
confidence: 99%
“…Foi demonstrado que as células T reguladoras (Tregs), com o fenótipo CD4 + CD25 + expressando o fator de transcrição Foxp3 que secreta IL-10 e TGF-β, estão associadas com a progressão e prognóstico desfavorável de vários tipos de câncer epitelial (Kobayashi et al, 2007;Petersen et al, 2006), incluindo o câncer cervical , baseado no fato de que a prevalência de células T reguladoras foi significativamente maior nas mulheres com carcinoma do que no tecido normal (Woo et al, 2008). Foi demonstrado que a alta taxa intraepitelial de CD8 + /Treg é fundamental para sobrevivência de pacientes com câncer cervical, sugerindo que uma expressiva infiltração de células T CD8 + pode superar os mecanismos de evasão do tumor (Jordanova et al, 2008).…”
Section: Resposta Imune Do Hospedeiro Contra O Hpv E Contra O Tumorunclassified